A Prototype Platform for Automated Chicken Feeding Control with an Embedded System - Natho, Parinya; Chamuthai, Likit; Boonying, Sangtong; Tantidontanet, Nantiya (International Journal of Advanced Science Computing and Engineering, 2023)
In this paper present a prototype platform for automated chicken feeding control with an embedded system. This prototype is an automated real-time chicken feeding mixing system that will help chicken farmers become more automated, which will be highly beneficial for the expansion of the chicken poultry farm in Phra Nakhon Si Ayutthaya, Thailand. This machine may take the role of a person in the chicken-feeding process, solving the farm's labor shortage. The apparatus for feeding chickens makes use of an Arduino Uno board as the heart of an embedded system controller. The two major components of this device are an Arduino that controls the servomotor opening for the food container and another Arduino that controls the servomotor opening for the food ingredients in a mixed food container. The prototype platform will have an alarm when the food ingredients are at the minimum quantity. This also helps the chickens get the amount of food and nutrients that are appropriate for their age while reducing labour costs, saving food, and controlling chicken feeding on time.